Computer-Aided Design technologies for computer systems and components - Leonov, Serhii Yuriiovych; Heiko, Hennadii Viktorovych (Національний технічний університет "Харківський політехнічний інститут", 2026)
A training manual includes theoretical and practical material related to the provision of computer-aided design systems. The basic information on the composition and principles of operation of computer-aided design systems is provided. The full cycle of designing complex hierarchical devices is described – from functional modeling and verification to design and obtaining printed circuit boards. For students of the specialty «Computer Engineering» and other technical specialties.
Keywords: computer systems; training manual; computer-aided design systems; computer-aided design; computer-aided manufacturing; computer-aided engineering